109 Effects of a Novel Dental Chew on the Oral Health Outcomes and Malodor of Adult Dogs. (21st September 2022) - Sieja, Kelly M; Oba, Patrícia M; Schauwecker, Amy; Hristova, Teodora; Keating, Stephanie; Somrak, Amy; Swanson, Kelly S
Abstract: Periodontal disease is a common oral health condition occurring in adult dogs, yet it is a preventable disease. The objective of this study was to evaluate the efficacy of a novel dental chew in adult dogs. All animal care and experimental procedures were approved by the University of Illinois Institutional Animal Care and Use Committee prior to experimentation. Twelve female beagles (mean age = 3.50 yr; mean BW = 8.77 kg) were used in a crossover design consisting of two 28-d periods. All dogs consumed the same commercial kibble diet throughout the study. Control dogs were offered only diet, while the treatment group received the diet plus a daily dental chew (Authority Dental Chew Orashield system formula containing sodium hexametaphosphate and texture) 4 h after their meal. On d0 of each period, teeth were cleaned by a veterinary dentist. Teeth were then scored for plaque, calculus, and gingivitis by the same veterinary dentist that was blinded to treatments on d28 of each period. Breath samples were measured for breath halitosis (volatile sulfur compounds) using a halimeter on d1, 7, 14, 21, and 27 of each period. All tooth scoring data were analyzed using the Mixed Models procedures of SAS. Halimeter data were analyzed using repeated measures using Mixed Models procedures. Oral calculus coverage and thickness were less (P< 0.05) in dogs consuming the novel chew than control dogs, while plaque was not different among groups. Gingivitis scores and gingival bleeding were also less (P< 0.05) in dogs consuming the novel chew compared with control dogs. Breath volatile sulfur compound concentrations were reduced (P< 0.05) in dogs consuming the novel chew than control dogs. Our results suggest that the novel dental chew tested in the study may aid in reducing the risk of periodontal disease in dogs.